Noncanonical Poly(A) Polymerase TENT4 Drives Expression of Subgenomic Hepatitis A Virus RNAs in Infected Cells - You Li; Ankit Gupta; Brian N. Papas; David Aponte-Diaz; Jayden M. Harris; Ichiro Misumi; Jason K. Whitmire; Craig E. Cameron; Marcos Morgan; Stanley M. Lemon (Viruses)
Both hepatitis B virus (HBV), an hepadnavirus with a DNA genome, and hepatitis A virus (HAV), a picornavirus, require the TRAMP-like host ZCCHC14-TENT4 complex for efficient replication. However, whereas HBV requires the nucleotidyltransferase activity of TENT4 to extend and stabilize the 3′ poly(A) tails of mRNA transcribed from its genome, the role played by TENT4 in HAV replication is uncertain. HAV proteins are synthesized directly from its genomic RNA, which possesses a 3′ poly(A) tail, with its length and composition presumably maintained by 3Dpol-catalyzed RNA transcription during its replicative cycle. Using nanopore long-read sequencing of RNA from infected cells, we confirm here that the length of the HAV 3′ poly(A) tail is not altered by treating infected cells with RG7834, a small molecule TENT4 inhibitor with potent anti-HAV activity. Despite this, TENT4 catalytic activity is essential for HAV replication. Surprisingly, nanopore sequencing revealed a low abundance of HAV subgenomic RNAs (hsRNAs) that extend from the 5′ end of the genome to a site within the 5′ untranslated RNA (5′UTR) immediately downstream of a stem-loop to which the ZCCHC14-TENT4 complex is recruited. These hsRNAs are polyadenylated, and their abundance is sharply reduced by RG7834 treatment, implying they are likely products of TENT4. Similar subgenomic RNAs were not identified in poliovirus-infected cells. hsRNAs are present not only in HAV-infected cell culture but also in the liver of HAV-infected mice, where they represent 1–3% of all HAV transcripts, suggesting their physiological relevance. However, transfecting exogenous hsRNA into TENT4-depleted cells failed to rescue HAV replication, leaving the functional role of hsRNA unresolved. These findings reveal a novel picornaviral subgenomic RNA species while highlighting mechanistic differences in the manner in which HAV and HBV exploit the host ZCCHC4-TENT4 complex for their replication.